Aplikasi Presensi Siswa Dan Guru Di SMK AN NUR Depok Menggunakan QR Code Berbasis Android - Irwansyah; Sofiana, Sofa (CV. Shofanah Media Berkah, 2023)
As a result of technological advances, especially in the world of informatics and the increasing number of emerging software created to overcome the problem of human error. In life, the system plays an important role so that what is needed should be obtained quickly, accurately and easily. Writing and the desire to design this attendance application so that the attendance process is all done in a computerized system. Therefore the researcher got the idea to solve the problem by creating an Android-based system that can connect directly to the school's server. This system is equipped with a QR Code to reduce abuse and manipulation of attendance by teachers and staff. In this study, researchers used Kodular to create an Android-based presence system, and presence reports can be printed from Google Spreadsheet. The hope of this research is that an Android-based attendance system with the QR Code feature can run well and meet the needs of the AN NUR Vocational School.